Winning the battles, losing the war? An assessment of counterterrorism in Malaysia - Bakashmar, Muhammad (Routledge, 2008)
This work addresses the structural weaknesses that threaten to derail counterterrorism efforts by the Malaysian government. It also highlights the links between various pre-September 11 security issues in Southeast Asia and the terrorism threat facing Malaysia at present. The limitations of the current counterterrorism approach by the government are highlighted. In addition, the paper identifies structural problems such as systemic corruption, weaknesses in border security,and inadequate private sector regulation as key areas of concern. The paper concludes by highlighting the symbiotic relationship between a successful counterterrorism campaign and the rule of law.